Assessment of climate change and its impact on cashcrops in Lwang Ghalel of Kaski district - Khadka, CB; Balla, MK; Tiwari, KR (Banko Janakari, 2013)
This paper focuses on climate change, its impact on cash crop production, perception of local people and their adaptation measures against the impacts of climate change in Lwang Ghalel Village Development Commitee (VDC) of Kaski district. Cash-crops such as tea, Amriso (broom grass) and cardamom were the main products in the study area. Primary data were collected through household survey with semi-structured questionnaires, interview with key informants, and formal and informal discussion. Thirty years meteorological data (rainfall and temperature) were collected from Narayani Basin Office, Pokhara to study the rainfall and temperature pattern. The rainfall pattern seemed to be increased at the rate of 2.74 mm per year while the mean annual maximum and minimum temperature also seemed to be increased by 0.064°C and 0.01°C per year, respectively. Tea was affected more due to climate change than other cash-crops. Amriso was the best adapted species against climate change due to its extended root system. DOI: http://dx.doi.org/10.3126/banko.v21i1.9061 Banko Janakari, Vol. 21, No. 1 2011; 31-34